B. –7 > x > 6
C. –6 < x < 6
D. –7 < x < 6
Answer:
D. –7 < x < 6
Step-by-step explanation:
(-534 +622 - 43) + (625 - 2? + 121 + 12)
Express the answer in standard form.
Answer:
801
Step-by-step explanation:
So we got the function of the graph f(x) = 2^x + 1 what you will need to do first is find the y-coordinates corresponding to x=1 and x=3 which can be found by substituting into the function. After that we can find the average rate of change using y2-y1/x2-x1.
f(1)=2^1+1 which would be equal to 3
1,3
f(3)=2^3+1 which would be equal to 9
3,9
9-3/3-1=6/2
6/2=3
The average rate of change is 3.
B. 2k^2 + k + 2
C. 2k^2 – k – 3
D. 2k^2 – k + 2
(2k+3)(k-1)
Use the distribute property
(2k)(k)+(2k)(-1)+(3)(k)+(3)(-1)
= 12k²-2k+3k-3
= 2k²+k-3
The answer is A
Good night
-112 = 7n
Answer:
n= -56/3
Step-by-step explanation:
Answer:
n -112 = 7n
Step-by-step explanation:
-6n= 112
-3n= 56
n= 56/ -3
n= -56/3